Identification of new serovar-specific detection targets against salmonella B serogroup using large-scale comparative genomics. (June 2021) - Ye, Qinghua; Shang, Yuting; Chen, Moutong; Pang, Rui; Li, Fan; Wang, Chufang; Xiang, Xinran; Zhou, Baoqing; Zhang, Shuhong; Zhang, Jumei; Wu, Shi; Xue, Liang; et al.
Abstract: Salmonella serotyping is a critical step for the identification of pathological isolates in humans and animals. Whole-genome analysis is a proven method for Salmonella serovars identification. In this study, we analysed 1668 genomic sequences of 23 serogroup B serovars and 129 genomic sequences of 80 non-target serovars to detect serovar-specific molecular targets for serogroup B (O:4 epitopes). Serogroup B is the most common serogroup found in China, whose presence is increasing in recent years. We identified five, eight, one, and seven new serovar-specific genes for Indiana, Derby, Typhimurium, and Agona serovars, respectively. We then designed specific PCR primer sets for these genes to validate our results. All target Salmonella serovars could be detected successfully by PCR in different types of food samples. The analytical sensitivity of PCR for 19 out of 21 pairs of primers was 10 1 –10 3 CFU/mL and 10 2 –10 5 CFU/g in pure cultures of the bacteria and artificially contaminated fresh pork samples, respectively. Furthermore, we performed a functional analysis of the newly-identified serovar-specific genes. We found that the function was unknown for most of the genes, although for some of them we were able to identify their generic functional categories (membrane protein genes and secreted proteins genes). Our findings revealed that whole-genome analysis is a valuable tool to identify new serovar-specific targets, which could be used to develop rapid and accurate molecular detection methods and provide additional information about different Salmonella serogroup B serovars. Highlights: We found 21 total specific genes for 4 different Salmonella serovars. PCR can be used for the detection of Salmonella serovars in food samples. The 21 genes were neither virulence-associated nor antibiotic resistance-associated.